Pemikiran politik dan kenegaraan Mohammad Natsir - Abdullah Firdaus,; Mohd. Nasir Omar,; Idris Zakaria, (Universiti Kebangsaan Malaysia, 2015)
Soon after gaining independence, discourse on making Syariah as a constitutional basis of state in Indonesia was widely regarded as a trending topic to discuss among politicians, Mohammad Natsir was one of them. This article aims to explore the political thought and the principle of government and state in the point of view of Mohammad Natsir. An approach carried on this study is using descriptive analysis and content analysis by focusing on documents and writings of the object studied. After a long study to his view, it shows that the concept of Islamic state, is not mere theoretical, as it’s practically applicable. The legal sovereignty upon Islamic state lies in its divine guidance which guarantees security, prosperity and justice to all people. Due to accepting the sovereignty of God as foundation for the constitution. Besides, government rules are supported by Islamic nationalism and theistic democracy guided by the principle of the unity of God (tawhid).